Pomegranate extract: a potential protector against aminoglycoside ototoxicity - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2014)
Objective: To investigate the effectiveness of pomegranate extract as protection against aminoglycoside ototoxicity. Design: Prospective, randomised, controlled, experimental study. Subjects: Eighteen Wistar albino rats were randomly allocated to 5 days of either: saline injections; gentamicin injections; or pomegranate extract (100 mu l/day via gavage) plus gentamicin injections. Distortion product otoacoustic emissions were tested before treatment and on day 3. After treatment, reactive oxygen species levels were measured in each rat's right cochlea and right kidney via chemiluminescence. Results: Baseline emission amplitudes were similar. Post-treatment emissions differed significantly in the two treatment groups (p<0.001). Cochlear reactive oxygen species levels were significantly higher in the gentamicin group (meanstandard deviation, 316.6 +/- 36.5 relative light units per mg) than the gentamicin plus pomegranate extract group (240 +/- 24.6 relative light units per mg) (p=0.004); control group levels were 119.1 +/- 10.3 relative light units per mg. Renal reactive oxygen species levels were similar for the control and gentamicin plus pomegranate extract groups (p = 0.59) but much higher in the gentamicin group (p = 0.004). Conclusion: Concurrent systemic pomegranate extract administration reduced reactive oxygen species level increases and otoacoustic emission changes, following aminoglycoside injection.
Keywords: Gentamicin; Punicaceae; Rats; Reactive Oxygen Species; Antioxidants; Otoacoustic Emissions; Spontaneous; Hearing Loss; Noise-Induced; REACTIVE OXYGEN; GENTAMICIN OTOTOXICITY; IN-VITRO; RATS; COCHLEA; JUICE; ANTIBIOTICS; OXIDATION; MELATONIN; TOXICITY